Intelligence versus Rationality (Annual of the Faculty of Philosophy in Skopje, 2017)
The last two decades cognitive psychologists have emphasized that rationality should be distinguished from intelligence, based on empirical evidence that even highly intelligent people lack the specific knowledge and strategies needed to think rationally. Many studies have demonstrated people ’s tendencies to display rational thinking errors in the domains of decision-making, probabilistic reasoning, causal reasoning, knowledge of risks, logic, practical numeracy, scientific thinking. Moreover, when rational thinking is correlated with intelligence, the correlation is usually quite modest and it is concluded that high-IQ people are only slightly more likely to spontaneously adopt disjunctive reasoning in situations that do not explicitly demand it. The paper mainly presents the perspective of Keith Stanovich regarding the intelligence versus rationality debate, showing how rationality is a more encompassing construct than intelligence. One of his key points is that IQ tests do not measure all cognitive faculties, they fail to assess individual differences in rational thought and it is necessary to introduce the concept of the rationality quotient (RQ) that refers to abilities to form rational beliefs and to take rational action. In this respect, Stanovich and his collaborators recently developed a prototype rational thinking test CART (Comprehensive Assessment of Rational Thinking). The structure and the psychometric characteristics of the test are described in the paper.
Keywords: INTELLIGENCE; RATIONALITY; KEITH STANOVICH; RATIONAL THINKING TEST